Occupational Risk Prevention among Intellectually Disabled People in Special Employment Centers - Paredes Gascón, Milagros; Fernández-Cid Enríquez, Matilde; Ruiz Figueroa, Mº Josefa (Cuadernos de Trabajo Social, 2012)
This article summarizes the working process and some of the main results of the research entitled “Training Needs in Occupational Risk Prevention for Intellectually Disabled Persons in Special Employment Centers.” The main interest is to analyze the importance of occupational risk prevention in protected work environments. Thus, we developed and implemented a cross-sectional study in three special employment centers of a non-profit Pro- Intellectually Disabled Persons Association in Madrid. The methodology included analysis of secondary sources, direct observation and non-structured interviews (with various stakeholders: directors, psychologists, work trainers, risk-prevention technicians, managers and disabled employees). The results show that occupational risk prevention training is graded as unsatisfactory by the workers, who also agree on their perception of the occupational risk as being low, which they attribute and correlate to the limited skill level required for their tasks. In some cases, interviewees indicate that it is the organization itself of the center where these disabled people provide their services which prevents the correct application of their knowledge of occupational risk prevention. The need for commitment on the part of those concerned in the process of labor integration of this group is emphasized, in order to tie in adaptive training with the overall organization of the work.